Assessment of Mangrove Ecosystem Damage And Species Distribution on Sulamanda Beach: Implications For Disaster Mitigation - Gemas, Agustina Prinarti; Roddialek, Pollo; de Rozari, Philiphi (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
This study aimed to analyze the types of damage to the mangrove forest ecosystem and address abrasion as part of disaster mitigation efforts on Sulamanda Beach, Mata Air Village, Kupang Regency. The research employed a quantitative and qualitative descriptive method using plot sampling for data collection. Observed data included mangrove density, frequency, and Important Value Index (IVI). The results identified six mangrove species: Avicennia marina, Avicennia alba, Lumnitzera racemosa, Rhizophora stylosa, Bruguiera parviflora, and Sonneratia alba. Among these, Bruguiera parviflora had the lowest density (1.7 stands/ha) and relative density (4.52%), while Sonneratia alba showed the lowest frequency (0.7 stands/ha) and relative frequency (12.3%). The IVI analysis revealed Sonneratia alba had the lowest value (14.14), indicating severe damage, primarily due to overharvesting for firewood. In contrast, Avicennia alba and Bruguiera parviflora exhibited the highest IVI values (55.04). These findings reflect the degraded state of mangrove communities, exacerbated by the perception of mangroves as common property with little value, leading to unsustainable exploitation. To mitigate abrasion and restore ecosystem health, community awareness programs and mangrove replanting initiatives are essential.